2003
DOI: 10.1074/jbc.m307635200
|View full text |Cite
|
Sign up to set email alerts
|

Role of the M-loop and Reactive Center Loop Domains in the Folding and Bridging of Nucleosome Arrays by MENT

Abstract: MENT is a developmentally regulated heterochromatin-associated protein that condenses chromatin in terminally differentiated avian blood cells. Its homology to the serpin protein family suggests that the conserved serpin reactive center loop (RCL) and the unique M-loop are important for its function. To examine the role of these domains, we studied the interaction of wild-type and mutant MENT with naked DNA and biochemically defined nucleosome arrays reconstituted from 12-mer repeats containing nucleosome posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 47 publications
2
47
0
1
Order By: Relevance
“…Our in vitro experiments revealed that the RCL is directly involved in MENT's ability to condense chromatin (58). The RCL is also indispensable for direct interaction with and specific inhibition of the protease cathepsin L in vitro (22).…”
Section: Resultsmentioning
confidence: 95%
“…Our in vitro experiments revealed that the RCL is directly involved in MENT's ability to condense chromatin (58). The RCL is also indispensable for direct interaction with and specific inhibition of the protease cathepsin L in vitro (22).…”
Section: Resultsmentioning
confidence: 95%
“…[208]12 NAs and [208]1 nucleosomes were prepared by mixing purified chicken erythrocyte core histones as described previously (40,54) except that gradient dialysis from 2.0 M NaCl to 250 mM NaCl was used for array reconstitution, followed by exhaustive dialysis to 5 mM NaCl. NAs were checked on DNP gels for a single major band, and the mean number of nucleosomes per array determined by electron microscopy (EM).…”
Section: Methodsmentioning
confidence: 99%
“…CAPs have multiple DNAand/or histone-binding sites that participate in local fiber folding in cis and fiber-fiber "bridging" in trans. Some CAPs, such as MeCP2, act as monomers (1,44), while others, such as MENT, are dimers (57), and the PCC complex is a heterooligomer (18). The biochemical mechanisms for achieving protein-mediated chromatin fiber condensation clearly are diverse.…”
mentioning
confidence: 99%